Baby Chimp - Debra Mostow Zakarin (U.S.A Grosset & Dunlap, 1996)
An adorable baby chimp finds termites for her breakfast, enjoys an afternoon tickle fight with friends, and finally builds a new nest for bedtime in this delightfully